Acute necrotising pancreatitis as the first and sole presentation of undiagnosed primary hyperparathyroidism (Indian Journal of Case Reports, 2019)
Primary hyperparathyroidism is a recognized, but rare, cause of acute pancreatitis. The pathophysiology of hypercalcemia-induced acute pancreatitis is not well known, but when this combination occurs, pancreatitis is likely to be severe and the degree of hypercalcemia may play an important role in this association. Therefore, the cause of hypercalcemia should be identified early. Surgical resection of the parathyroid adenoma is the ultimate therapy. We report two cases with severe acute necrotizing pancreatitis associated with hypercalcemia. The cause of hyperparathyroidism was a benign parathyroid adenoma. We highlight the drawbacks in delaying the diagnosis of primary hyperparathyroidism in patients with acute pancreatitis as the sole clinical presentation.